Multiple dermatofibromas in a girl withsystemic lupus erythematosus. - Garofalo, L.; Mazzotta, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
Multiple dermatofibromas have been so far reported in systemic lupus erythematosus and in HIV infection. A further case of multiple dermatofibromas in a girl affected by systemic lupus erythematosus and followed up from the age of twelve is reported and its pathogenesis is discussed.